2017
DOI: 10.4103/0019-5413.197545
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of posterior slope of tibial plateau in adult Eastern Indian population

Abstract: Background:Upper surface of the proximal tibial end, tibial plateau, has a slope directed posteroinferiorly relative to the long axis of the middle of the shaft. It has important consideration in surgeries such as knee arthroplasty, high tibial osteotomy, and medical imaging of the knee joint. The aim of the present study was to estimate the tibial plateau angle (TPA) by plain radiograph in the adult Eastern Indian population as during literature review, we were unable to find any study, except one (without sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Cinotti et al [ 20 ] and Han et al [ 22 ] also reported no gender difference in medial and lateral PTS angles in Italian and South Korean participants. This is consistent with several radiographic studies conducted in different ethnic groups [ 2 , 12 , 26 ]. In contrast, Hashemi et al [ 15 ] found that the medial and lateral PTS angles were greater in women compared to men, potentially rendering them more susceptible to developing an ACL injury and ATT [ 5 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Cinotti et al [ 20 ] and Han et al [ 22 ] also reported no gender difference in medial and lateral PTS angles in Italian and South Korean participants. This is consistent with several radiographic studies conducted in different ethnic groups [ 2 , 12 , 26 ]. In contrast, Hashemi et al [ 15 ] found that the medial and lateral PTS angles were greater in women compared to men, potentially rendering them more susceptible to developing an ACL injury and ATT [ 5 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…A steeper PTS increases the likelihood of sustaining an ATT [ 7 , 30 ]. Higher BMI was linked to an increased risk of ACL tear in the presence of a steeper lateral PTS [ 31 ], because a steeper PTS facilitates the tibia in translating anteriorly, which results in overtightening of the ACL, one of the main structures responsible for knee stability [ 2 , 3 ]. It is possible that the extra load on the knee joint from obesity may increase the wear and tear process of the cartilage and bone surfaces of the knee, a primary weight-bearing joint, leading to alteration of the proximal tibia and subsequent modification of the PTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was no significant difference in PTS between males and females (P >0.05). Likewise, Katchy et al [ 13 ] and Medda et al [ 23 ] found no sexual dimorphism among Nigerian and Indian subsets, respectively. MRI of the knee is the gold standard modality by which medial and lateral tibial plateaus can be assessed separately [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…Differences in the PTS among ethnic groups have already been reported [ 13 - 15 , 20 , 23 ]. Table 6 presents PTS angles measurements among different populations, using a similar reference axis (ATC).…”
Section: Discussionmentioning
confidence: 98%